El derecho internacional y los ODS: la eficacia de su cumplimiento a seis años de su puesta en marcha - Florabel Quispe-Remón (Revista Iberoamericana de Estudios de Desarrollo)
In this paper, it is briefly addressed, first, the principles that govern the relations of States since the birth of contemporary international law, to analyse their content and the commitment of States to them. Then, it will be analysed if, within these principles, we are able to find some aspects that today are part of the Sustainable Development Goals (SDGs) and, if so, to what extent States would be obliged to fully comply and achieve their effectiveness. Secondly, it will examine the progress in the fulfilment of the 17 SDGs, almost six years after their launch in 2015, through certain indicators.